Atomic and molecular data for spacecraft re-entry plasmas. (17th May 2016) - Celiberto, R; Armenise, I; Cacciatore, M; Capitelli, M; Esposito, F; Gamallo, P; Janev, R K; Laganà, A; Laporta, V; Laricchiuta, A; Lombardi, A; Rutigliano, M; et al.
Abstract: The modeling of atmospheric gas, interacting with the space vehicles in re-entry conditions in planetary exploration missions, requires a large set of scattering data for all those elementary processes occurring in the system. A fundamental aspect of re-entry problems is represented by the strong non-equilibrium conditions met in the atmospheric plasma close to the surface of the thermal shield, where numerous interconnected relaxation processes determine the evolution of the gaseous system towards equilibrium conditions. A central role is played by the vibrational exchanges of energy, so that collisional processes involving vibrationally excited molecules assume a particular importance. In the present paper, theoretical calculations of complete sets of vibrationally state-resolved cross sections and rate coefficients are reviewed, focusing on the relevant classes of collisional processes: resonant and non-resonant electron-impact excitation of molecules, atom–diatom and molecule–molecule collisions as well as gas-surface interaction. In particular, collisional processes involving atomic and molecular species, relevant to Earth (N2, O2, NO), Mars (CO2, CO, N2 ) and Jupiter (H2, He) atmospheres are considered.